Spontaneous diffusion of information in online social networks - Russ, C. (NTU "KhPI", 2008)
Online Social Networks (OSN) are new types of web services which provide online communities an environment to gather and meet virtually. The online users are connected to each other via links of trust and utilize the features of the OSN to interact and communicate in an easy socio-technical way. Hence these virtual networks of social relationships have a high potential for influential decision-making and the word of mouth spread of information, but also for spreading fads, rumors, and erroneous information. The power of these new forms of social networks is also recognized by service providers, marketers and vendors of consumer goods. They would all like to (mis) use these existing communication channels to spread product placements, advertising and promotions directly to the connected users. However, just like the old economy businesses, not all attempted marketing initiatives are successful. Most of them fail or do notreach the desired audience. This paper tries to explain why OSN are a good environment for spontaneous diffusion of information and what phases of development need to beaccomplished to reach the optimal spreading rate for one piece information. Therefore, we start with a look at the "Hype Cycle" model of Gartner to explain over-enthusiasm for new technology adoptions. Next we introduce the concept of "social contagion" and the infections spread of information. After a short introduction of OSN, we try to illustrate the phases of a social online contagion development process which can lead to spontaneous and uncontrolled diffusion of information, messages or ideas. The core statement of our approach is that online individuals tend to behave collectively if they observe the virtual behaviors and actions of others. This principle of "other-directedness" can generate a chain reaction of infectious imitation which can sometimes spread uncontrolled through the interconnected social network like an epidemic. This helps to explain why some online information waves can grow extraordinarily high and others fall.

Онлайнові соціальні мережі (ОСМ) є новими типами веб-сервісів, які пропонують онлайновим суспільствам середовище для гуртування та віртуального спілкування. Як наслідок, такі віртуальні мережі соціальних зв'язків мають високий потенціал для впливового прийняття рішень та розповсюдження інформації "з вуст в уста", але, з іншого боку, вони також можуть розповсюджувати чутки, плітки та некоректну інформацію. Потенціал цих мереж також розпізнається сервіс-провайдерами, маркетологами та виробниками товарів. Вони усі бажають використовувати ці існуючі комунікаційні канали для розповсюдження реклами продуктів безпосередньо користувачам. Але не усі такі спроби є успішними. Ця робота робить спробу пояснити, чому ОСМ є добрим середовищем для спонтанного розповсюдження інформації, та які етапи повинні бути виконані для досягнення оптимального рівня розповсюдження для одного елемента інформації. Ми починаємо з розгляду моделі гіперциклів Гартнера, яка пояснює надмірний ентузіазм при впровадженні нових технологій. Далі ми вводимо концепцію "соціального забруднення" та інфекційного розповсюдження інформації. Базова ідея нашого підходу полягає в тому, що онлайнові індивідуали прихильні до колективної поведінки, тобто вони спрямовані на віртуальну поведінку та дії інших. Цей принцип "спрямованості на інших" може генерувати ланцюгову реакцію інфекційних імітацій які інколи можуть розповсюджуватись неконтрольовано через соціальні мережі, подібно до епідемії.
Keywords: онлайнові соціальні мережі; веб-сервіси; віртуальне спілкування; модель гіперциклів Гартнера